PENGARUH PEMBERIAN KOMPOS TANDAN KOSONG KELAPA SAWIT DAN PUPUK N, P, K TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN MELON (Cucumis melo L.)”. - Mustaqim, Rahmat; Yulia, Arnis En; ', Armaini (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The cultivation of plants melon in Riau based on condition growing is in line, but there were several obstacles such as the land in riau levels of fertility land which is low.This research aims to determine the combination of doses of an empty oil palm bunches of compost and fertilizer n, p, k the best against growth and melon crop production (Cucumis melo L.) in the trial gardenFaculty of Agriculture, University of Riau. This research was conducted on February 2015 until June 2015. The research has been carried out experimentally in the form of Randomized Completely Design Factorial 2 x 4. The first factor is the dose compost of  oil palm empty fruit bunches consist of two levels and the second factor is the dose of N (ZA) fertilizer, P (TSP) fertilizer and K (KCL) fertilizer consist of four levels. Data analyzed by ANOVA and further tested using by Duncan`s New Multiple Range Test (DNMRT) at the level of 5%.parameter made were higher plants, diameter of stem, appears the male flowers and female flowers, diameter of fruits, weight of fruits per sampel and weightof fruits per plot. The results showed the treatment compost of oil palm empty fruit bunches and N, P, K fertilizer significantly affect on the plants height, diameter of stem, appears the male flowers and female flowers but not significant on the diameter of fruits, weight of fruits per sampel and weightof fruits per plot. The application compost of oil palm empty fruit bunches with dose of 20 tons/ha and ZA fertilizer 120 kg/ ha, TSP fertilizer 80 kg/ha, KCl 200 kg/ ha is the best dose in order to enchance growth and production of melon. Keywords: melon, compost of oil palm empty fruit bunches and N, P, K fertilizer